Recurrence Rate and Risk Factors for Apical Prolapse After Sacrospinous Ligament Fixation: A Prospective Cohort Study - Musa Kayondo; Rogers Kajabwangu; Onesmus Byamukama; Brenda Ainomugisha; Kalyebara Paul Kato; Leevan Tibaijuka; Henry M. Lugobe; Verena Geissbuehler (Cureus, 2026)
Objective: We aimed to determine the one-year recurrence rate of apical prolapse following sacrospinous ligament fixation and to identify clinical and surgical risk factors associated with recurrence in a low-resource setting. Methods: This was a prospective cohort study of women who underwent sacrospinous ligament fixation as part of surgery for apical prolapse at the urogynecology unit of Mbarara Regional Referral Hospital (MRRH) in Uganda. The surgeries performed included vaginal hysterectomy with sacrospinous ligament vault fixation, sacrospinous ligament hysteropexy, and sacrospinous ligament vault fixation for those with posthysterectomy vaginal vault prolapse. Concomitant procedures such as anterior or posterior repair, or both, were performed for women with prolapse in other compartments. The women were followed up for a period of one-year post-surgery. Recurrence was assessed with the women in lithotomy position under maximum strain using the Pelvic Organ Quantification (POP-Q) system. Recurrence was defined as apical prolapse of ≥POP-Q stage II. Multivariable log-binomial regression was performed to determine risk factors for recurrence. Results: A total of 123 participants were enrolled in this study, of which 111 (90.2%) completed follow-up. The mean age was 53.1 (SD ±13.6) years. The majority of apical prolapse was uterine (94.6%) and classified as POP-Q stage III (58.6%). The recurrence rate was 19.8% (22/111, 95% CI: 13.4-28.4). Risk factors for apical prolapse recurrence included body mass index (BMI) >25 kg/m2 (relative risk (RR) = 6.02; 95% confidence interval (CI): 2.05-17.67; p = 0.001) and post-operative complications (RR = 19.87; 95% CI: 5.77-68.47; p < 0.001). Undergoing vaginal hysterectomy as part of the prolapse surgery was found to be protective (RR = 0.09; 95% CI: 0.03-0.25; p < 0.001). Conclusions: Apical prolapse recurrence after sacrospinous ligament fixation is common in this setting. To reduce the risk of recurrence, management protocols should prioritize prevention and timely management of postoperative complications, and counseling for weight optimization. Furthermore, vaginal hysterectomy should be considered in uterine prolapse where uterine sparing surgery is not required.
Keywords: apical prolapse; recurrence; risk factors; sacrospinous ligament fixation; uganda